Treatment of severe neurological defi cits with IgG depletion through immunoadsorption in patients with Escherichia coli O104:H4-associated haemolytic uraemic syndrome: A prospective trial - Greinacher, Andreas; Friesecke, Sigrun; Abel, Peter; Dressel, Alexander; Stracke, Sylvia; Fiene, Michael; Ernst, Friedlinde; Selleng, Kathleen; Weissenborn, Karin; Schmidt, Bernhard M.W.; Schiffer, Mario; Felix, Stephan B.; et al. (Lancet, 2011)
Background In May 2011, an outbreak of Shiga toxin-producing enterohaemorrhagic E coli O104:H4 in northern Germany led to a high proportion of patients developing post-enteritis haemolytic uraemic syndrome and thrombotic microangiopathy that were unresponsive to therapeutic plasma exchange or complement-blocking antibody (eculizumab). Some patients needed ventilatory support due to severe neurological complications, which arose 1 week after onset of enteritis, suggesting an antibody-mediated mechanism. Therefore, we aimed to assess immunoadsorption as rescue therapy. Methods In our prospective non-controlled trial, we enrolled patients with severe neurological symptoms and confi rmed recent E coli O104:H4 infection without other acute bacterial infection or raised procalcitonin concentrations. We did IgG immunoadsorption processing of 12 L plasma volumes on 2 consecutive days, followed by IgG replacement (0•5 g/kg intravenous IgG). We calculated a composite neurological symptom score (lowest score was best) every day and assessed changes before and after immunoadsorption. Findings We enrolled 12 patients who initially presented with enteritis and subsequent renal failure; 10 (83%) of 12 patients needed renal replacement therapy by a median of 8•0 days (range 5-12). Neurological complications (delirium, stimulus sensitive myoclonus, aphasia, and epileptic seizures in 50% of patients) occurred at a median of 8•0 days (range 5-15) and mandated mechanical ventilation in nine patients. Composite neurological symptom scores increased in the 3 days before immunoadsorption to 3•0 (SD 1•1, p=0•038), and improved to 1•0 (1•2, p=0•0006) 3 days after immunoadsorption. In non-intubated patients, improvement was apparent during immunoadsorption (eg, disappearance of aphasia). Five patients who were intubated were weaned within 48 h, two within 4 days, and two patients needed continued ventilation for respiratory problems. All 12 patients survived and ten had complete neurological and renal function recovery. Interpretation Antibodies are probably involved in the pathogenesis of severe neurological symptoms in patients with E coli O104:H4-induced haemolytic uraemic syndrome. Immunoadsorption can safely be used to rapidly ameliorate these severe neurological complications. Funding Greifswald University and Hannover Medical School. Copyright © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-11-12